Konstitusionalitas dan Ideologi dalam Sistem Pemilu: Tafsir Moral Pancasila pada Sistem Representasi Proporsional - Syafruddin Muhtamar; Fahri Bachmid (CV. Social Politic Genius (SIGn), 2021)
This study aims to examine and analyze the constitutionality of the electoral system to the relevance of the philosophische grondslag and staatsfundamentalnorm of Pancasila and to investigate the constitutional ideological degree of the electoral system in Indonesia. This study uses normative legal research with a statute, historical, and comparative approaches. The collection of legal materials is carried out using a literature study technique. The collected legal material is then qualitatively analyzed to describe the problem and answer study purposes. The results show that the constitutionality of the PR system in Indonesian state governance is an effort to create an inclusive and democratic government. However, since the Reform Era and the post-amendment of the 1945 Constitution, the moral values of Pancasila are embedded in the preamble of the 1945 Constitution as philosophische grondslag and staatsfundamentalnorm, its implementation has not been realized in every subject matter. Additionally, Pancasila should be the standard measure of the ideological degree of the electoral system in Indonesia. Therefore, it is recommended that the Government and the House of Representatives prioritize implementing Pancasila’s moral values in the electoral system by amending the 1945 Constitution and Law Number 7 of 2017. Implementing Pancasila’s values must be concretely realized in each main subject regulated in the body of the 1945 Constitution and the norms of Law Number 7 of 2017. Furthermore, systematic evaluations of Indonesia’s electoral system should be carried out periodically to ensure alignment between the electoral system and Pancasila as the country’s ideological foundation. Thus, the design of the electoral system will become an ideological means for realizing national goals based on Pancasila ideology in the future.